From Extensive Reading to Advanced Reading Skills: A student’s narrative - Mahmud, Muzdalifah; Mokoolang, Adi Tia; Achmad, Syarifuddin (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study examines the relationship between extensive reading habits and the reading skills of English students at Universitas Negeri Gorontalo. Extensive reading is a reading practice that involves reading a substantial quantity of material at an appropriate level to gain a comprehensive understanding. This approach is believed to enhance reading abilities and foster a positive reading habit. This study focuses on reading as a daily practice rather than as a discrete classroom activity. The study employs interviews with three students who engage in extensive reading to ascertaintheir attitudes toward reading, reading frequency, reading preferences, and sources of motivation. These students exhibit positive attitudes toward reading, read frequently, enjoy various types of books, and are motivated by their family and academic environment. These habits lead to better vocabulary and reading comprehension. The study concludes that extensive reading helps improve reading skills and recommends that students make it a regular part of their lives and that teachers support and encourage extensive reading.